LITERASI SAINS PADA BAHAN AJAR ILMU PENGETAHUAN ALAM DAN SOSIAL (IPAS) SEKOLAH DASAR - Rosyida, Alifia; Qorinasari, Dian; Indriasari, Pipit Saraswati; Ardhiansyah, Wildhan; Hidayati, Yulia Maftuhah; Desstya, Anatri (JURNAL PENDIDIKAN DASAR PERKHASA: Jurnal Penelitian Pendidikan Dasar, 2024)
Low scientific literacy is caused by learning activities that emphasize the aspect of remembering material and pay less attention on the processes and practices in real life, as well as learning that pays less attention on discovery. This research aims is to analyze and describe the content of science teaching materials based on indicators of scientific literacy ability. This research applied a qualitative approach with a content analysis design. The subjects of this research were teachers at SD Negeri Polokarto 03. Data collection techniques using triangulation of sources and techniques. Data collection tools are observation, interviews and documentation. The results of the content analysis show that overall of the teaching materials are in the fairly good category for containing scientific literacy; The content of teaching materials can also be integrated with natural potential in everyday life; and teaching materials that include elements of motivation and communication as well as local approaches are able to increase scientificÂ  literacy competence and science subjects.